Survey of Inmates in State and Federal Correctional Facilities, (United States), 2004 ([Verlag nicht ermittelbar], 2007)
This survey provides nationally representative data on inmates held in state prisons and federally-owned and operated prisons. Through personal interviews conducted from October 2003 through May 2004, inmates in both state and federal prisons provided information about their current offense and sentence, criminal history, family background and personal characteristics, prior drug and alcohol use and treatment programs, gun possession and use, and prison activities, programs, and services. Prior surveys of State prison inmates were conducted in 1974, 1979, 1986, 1991, and 1997. Sentenced federal prison inmates were interviewed in the 1991 and 1997 surveys.